TRANSFORMATION OF STUDENTS’ CHARACTER THROUGH THE STRATEGIC ROLE OF ISLAMIC EDUCATION TEACHERS AT SARDONOHARJO 1 PUBLIC ELEMENTARY SCHOOL - Hilda; Mulyadi; M Hajar Dewantoro; Siregar , Nurlina (At-Thullab : Jurnal Mahasiswa Studi Islam, 2025)
This study aims to analyze the strategic role of Islamic Education (PAI) teachers in transforming students’ character through Islamic-based character education at Sardonoharjo 1 Public Elementary School. Using a qualitative approach, data were collected through observation, interviews, and documentation. The results show that Islamic Education teachers serve as educators, role models, facilitators, motivators, and evaluators in shaping students’ morals and ethics. Although challenges such as limited instructional time and negative external influences exist, integrative learning strategies have proven effective in instilling Islamic values. This study recommends enhancing collaboration among schools, teachers, and parents to strengthen students’ Islamic character education.